Evaluación de desempeño de dos diseños de lechadas de cemento para sistemas de recuperación térmica en el Campo Chichimene ubicado en la cuenca de los Llanos Orientales (2014)
The performance of two-cement slurry designs for thermal recovery systems in Chichimene oilfield were evaluated through laboratory tests. Design ranges were established for the project, taking into account the conditions of a real drilled well in the oilfield, as well as the quality standards required by Ecopetrol S.A. for this kind of projects, for both API properties and mechanical properties. According to obtained results, technology B is the one which best fit the requirements for the project, therefore lt's recommended for use in cementing wells of this oilfield or any other with similar conditions to the chosen well, used to establish the properties ranges.